The identity of the Arab moral mind according to Al-Jabri: an analytical and comparative study - Anayat, Abdul Karim (Journal of Social Sciences (COES&RJ-JSS), 2021)
We can only admit the existence of worthy contemporary Arab moral writings, and we have a good example in the work of Al-Jabri's Archeology. As he was able to identify the local and foreign elements of the Arab moral mind. Comparing this attempt with the most important Arab ethical book written at the beginning of the third millennium (2000) allows us to see the moral writing strategies that are inseparable from the philosophical, doctrinal and methodological choices. Therefore, we have devoted a comparative space that reveals the results of doctrinaire in moral writing and the difference between the historiography of ethics and the establishment of an original moral theory. In fact, the comparison we made also indicates ethical choices ranging from the theory of moral identity to the theory of the moral process. This is what was studied in the last component. The general problem on which the course of the study is related to the following question: How can we establish an Islamic moral theory of unified origin and purpose despite the fact that the Islamic identity is multiple in its components?